Beyond Digital Access: Teachers’ and Students’ Perceptions of Technology Integration in Rural EFL Classrooms in Indonesia - Rizqi Claudia Wardani; Muftihaturrahmah Burhamzah; Nurdin Noni (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study investigates the reality of technology integration in English as a Foreign Language (EFL) classrooms at SMA 5 Baraka, Enrekang, Indonesia. Although educational technology has become a central component of contemporary pedagogy, implementation in peripheral and resource-constrained schools often remains inconsistent. The study aimed to explore actual classroom practices, teacher and student perceptions, and contextual barriers affecting sustainable integration. A qualitative case study design was employed. Data were collected through classroom observations, semi-structured interviews, student focus-group discussions, and document analysis. Data were analyzed thematically through coding, categorization, and triangulation. The findings indicate that technology integration occurred primarily through smartphones, projectors, WhatsApp, YouTube, and presentation software. Teachers perceived technology as beneficial for increasing motivation, facilitating listening exposure, and improving instructional efficiency. Students expressed positive attitudes toward multimedia-supported learning environments. However, unstable internet connectivity, inadequate devices, limited professional training, time constraints, and inconsistent institutional support restricted deeper pedagogical innovation. Most practices remained at functional levels of substitution and augmentation rather than transformative use. The study concludes that meaningful technology integration requires infrastructure readiness, sustained teacher development, and context-sensitive policy support. These findings contribute empirical insight into digital inequality and pedagogical adaptation in Indonesian EFL settings.